Are positive changes in potential determinants associated with increased fruit and vegetable intakes among primary schoolchildren? Results of two intervention studies in the Netherlands: The Schoolgruiten Project and the Pro Children Study - te Velde Saskia J; Tak Nannah I; Brug Johannes (BMC, 2008)
Abstract Background To investigate if positive changes or maintenance high scores on potential behavioral determinants of fruit and vegetable (F&V) intake are associated with increased or maintenance favorable levels of F&V intake frequency in the same time lapse or later in time. Data were used from two intervention studies in the Netherlands: the Schoolgruiten Project and the Pro Children Study. Methods A design with baseline and two follow-up measurements. 344 children of the Dutch Schoolgruiten Project and 258 children of the Pro Children Study completed questionnaires, including questions on general demographics, usual F&V intake frequency, important potential determinants of F&V intake, such as taste preferences of F&V, availability of F&V, knowledge of recommended intake levels of F&V, self-efficacy for eating F&V, and parental influences for eating F&V. Three different associations between changes in determinants of F&V intake and changes in F&V intake frequency were assessed by multilevel multinomial regression analyses. Results Results of one of the investigated associations indicated that in both studies behavior change (increase in F&V intake frequency) was preceded by changes in the following variables; liking of fruit, parental facilitation of vegetables, family rules for eating vegetables and availability at home of vegetables. Furthermore, changes in F&V intake frequency preceded changes in liking of F&V later in time. Conclusion In accordance with behavior change theories, the present study provides some evidence that behavior change was preceded by changes in certain potential determinants of F&V intake. Potential determinants of F&V intake that appear to be important to induce behavior change were liking of fruit, parental facilitation of vegetables, family rules for eating vegetables and availability at home of vegetables. Some evidence was also found that behavior changes may precede changes in presumed determinants of F&V intake, such as liking of F&V.